FOR A HISTORY OF LISTENING IN THE BRAZILIAN SCHOOL: THE IDEAS DISPOSED IN THE TEACHING GUIDES OF THE ANCIENT CHORAL SINGING GROUPS - Constantino, Paulo [UNESP] (Univ Estadual Paulista-unesp, Fac Ciencias Letras Assis, 2018)
It reconstructs the paths of musical listening in the Brazilian school, composing a historiography on elements that are minimal, through bibliographical research. The emphasis is on the period of development of the 'Canto Orfeonico' [choral singing groups between the decades of 1930-1960] in the country, which presents the ideas about listening present in seven guides published at the time. The predominance of performance and civic education in the groups relegated the listening as a pedagogical activity to a secondary plane, and its recognition will be placed only after the second half of the twentieth century: for technological reasons, with the popularization of recordings; and by the introduction of a literature that would recognize the basic character of the activities in musical education.
Keywords: Music history; Listening; Schooling culture; Choral groups [Orfeonico's Singing Groups]